A study of waste minimization at Fujikura Federal Cables Sdn. Bhd - Yeap, Chuen Theng (2013)
This study is divided into five chapters and each chapter talks about different contents which are aligned with the aims and objectives of the study. Chapter 1 explains the introduction of waste, research background of waste minimization in Malaysia, problem statement, project objectives, scope of project, and the importance of research. Chapter 2 presents a review of literature regarding the study. Chapter 3 discusses the methodology used in this study. The results and findings of the study are presented in Chapter 4. Finally, conclusion, problems, and recommendations for this study are covered in Chapter 5